Dielectric metasurface-assisted terahertz sensing: mechanism, fabrication, and multiscenario applications - Chen Xueer; Xin Shanshan; Liu Qing; Meng Yihan; Yu Daquan; Tseng Ming Lun; Ye Longfang (Nanophotonics)
Terahertz (THz) technology has attracted significant global interest, particularly in sensing applications, due to its nonionizing feature and sensitivity to weak interactions. Recently, owing to the advantages of low optical loss and the capability to support both electric and magnetic high-quality factor (high-Q) resonances, dielectric metasurfaces have emerged as a powerful platform for multiscenario terahertz sensing applications. This review summarizes recent advancements in dielectric metasurface-assisted THz sensing. We begin with an overview of the mechanisms and properties of dielectric metasurfaces with high-Q factors. Next, we discuss typical fabrication techniques for these terahertz dielectric metasurfaces. We then explore the diverse terahertz sensing applications across various scenarios, including biomolecule sensing, biomedical detection, environmental monitoring, and chiral sensing. Finally, we provide perspectives on the future development of this promising research field.